The use of meeting tools to make an online event: The CTRL+E experience - Medeiros, Elizabet M. Spohr de; Villacorta, Kely D. V.; Moreno, Felipe A. G.; Salviano, Artur I. A.; Silva, Matheus Gomes; Pedrosa, João Victor; Cavalcanti, Daniel de Queiroz; Nascimento, Matheus W. T. (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and EducationDO - 10.5753/wave.2020.212083, 2021)
This article describes the experience acquired in the use of tools for recording remote meetings, video editing and transmissions used in the execution of CTRL+E 2020, transforming it into a 100% online event.